2022
DOI: 10.1186/s40168-021-01197-5
|View full text |Cite
|
Sign up to set email alerts
|

Inhalable antibiotic resistomes emitted from hospitals: metagenomic insights into bacterial hosts, clinical relevance, and environmental risks

Abstract: Background Threats of antimicrobial resistance (AMR) to human health are on the rise worldwide. Airborne fine particulate matter (PM2.5), especially those emitted from hospitals, could serve as a substantial yet lesser-known environmental medium of inhalable antibiotic resistomes. A genome-centric understanding of the hosting bacterial taxa, mobility potential, and consequent risks of the resistomes is needed to reveal the health relevance of PM2.5-associated AMR from clinical settings. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 76 publications
2
42
1
Order By: Relevance
“…9 ARGs harbored in PM can be a resource providing antibiotic resistance from the "One Health" perspective. 10 As people spend approximately 90% of their time on indoor activities in modern life, 11 the indoor environment is vital for public health. Therefore, understanding the prevalence, status, and transmission mechanism of ARGs in indoor dust is of great importance for assessing the exposure risk of humans to antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 ARGs harbored in PM can be a resource providing antibiotic resistance from the "One Health" perspective. 10 As people spend approximately 90% of their time on indoor activities in modern life, 11 the indoor environment is vital for public health. Therefore, understanding the prevalence, status, and transmission mechanism of ARGs in indoor dust is of great importance for assessing the exposure risk of humans to antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has revealed that the air environment is a large reservoir of ARGs. Airborne transmission has been contempered to be a crucial route for ARGs’ spread and exposure. , Particle matter (PM), which is an important airborne contaminant, offers a large volume of adhering sites, thus enhancing the stability of ARGs in the air . ARGs harbored in PM can be a resource providing antibiotic resistance from the “One Health” perspective . As people spend approximately 90% of their time on indoor activities in modern life, the indoor environment is vital for public health.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, a lack of correlation was reported between microbiomes and resistomes in the intestinal tracts of migration birds ( 42 ). Few reports have investigated the correlation between APM microbiomes and resistomes, except for a recent publication on Microbiome that collected emitted bioaerosols of a hospital ( n = 19) in Guangzhou city and urban PM 2.5 ( n = 10) in the same city for analysis ( 43 ). A significant correlation was found between APM microbiomes and resistomes in the hospital but not for urban APM samples.…”
Section: Discussionmentioning
confidence: 99%
“…These included rpoB2 (tuberculosis drugs), vanR, ugd, blaOXA, class-a, msrA, tetL, and bacA. 76 These ndings suggest that human activity inside of a hospital, and any indoor environment, could lead to an increase of ARGs in the air, and therefore increase the likelihood of exposure to ARGs.…”
Section: Hospitalsmentioning
confidence: 97%
“…Interestingly, they also found that the difference between the relative abundance of ARGs in the urban and hospital settings was much more pronounced in the summertime, especially for MLS and β-lactam. 76 Another hospital study in China showed that the diversity of ARGs was higher during the winter, but the abundances were comparable. In this study, samples were collected from the air filtration system in the hospital and could have been more affected by seasonal changes in operation rather than by the weather itself.…”
Section: Season and Weathermentioning
confidence: 99%